2000
DOI: 10.1093/humrep/15.9.1932
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to phosphatidylethanolamine and phosphatidylserine are associated with increased natural killer cell activity in non-male factor infertility patients

Abstract: Antiphospholipid antibodies (APA) have been identified in patients with recurrent pregnancy loss and IVF failure. Of these, antiphosphatidylethanolamine (aPE) and antiphosphatidylserine (aPS) may have special significance. A link between increased natural killer cell activity (NKa+) and trophoblast cell apoptosis has also been reported. This study was undertaken to determine how the APA profile was associated with peripheral NK cell activity. We evaluated 197 female IVF candidates for APA and NKa. Eighty-nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 29 publications
0
13
1
Order By: Relevance
“…They may affect implantation, placentation, and early embryonic development, as the antibody binds to b2 GP I and is responsible for breakdown of the phospholipids' adhesion molecules between different elements of trophoblast [10]. A 2000 meta-analysis concluded that there was no significant association between the presence of aPLs and either the clinical pregnancy rate or live birth rate in in vitro fertilization patients [11], but in this study, other antibodies besides aCL and LA, such as antiphosphatidylserine and antiphosphatidylethanolamine, had a positive relationship with increased natural killer cell activity among infertile women with non-male factor undergoing in vitro fertilization [12], and there is an elevated prevalence of these new antibodies among in vitro fertilization failure patients [13]. Further studies should be conducted to help us better understand the association between aPLs and infertility.…”
Section: Antiphospholipid Syndrome and Infertilitycontrasting
confidence: 51%
“…They may affect implantation, placentation, and early embryonic development, as the antibody binds to b2 GP I and is responsible for breakdown of the phospholipids' adhesion molecules between different elements of trophoblast [10]. A 2000 meta-analysis concluded that there was no significant association between the presence of aPLs and either the clinical pregnancy rate or live birth rate in in vitro fertilization patients [11], but in this study, other antibodies besides aCL and LA, such as antiphosphatidylserine and antiphosphatidylethanolamine, had a positive relationship with increased natural killer cell activity among infertile women with non-male factor undergoing in vitro fertilization [12], and there is an elevated prevalence of these new antibodies among in vitro fertilization failure patients [13]. Further studies should be conducted to help us better understand the association between aPLs and infertility.…”
Section: Antiphospholipid Syndrome and Infertilitycontrasting
confidence: 51%
“…It has been demonstrated that APE and APS positivity in female infertility was associated with increased NK cell activity and decreased IVF success, which did not happen if the APE/APS were found in isolated male factor infertility. Thus, again in this study, APL were considered not as causally related to reproductive failure, rather as markers or intermediaries of an underlying abnormal cellular immunity [73].…”
Section: Nk Cells and Autoantibodiesmentioning
confidence: 95%
“…Women with APS demonstrate high level of NK cells in the peripheral blood and endometrium. It is possible that disturbed synthesis of mediator molecules which participate in embryo adhesion and invasion by NK cells is one of the causes of disturbed signaling interaction between the blastocyst and endometrium on the earliest implantation stages (Quenby et al, 2009;Sher et al, 2000). APLAs stimulate PAI-1 synthesis that may cause disturbed degradation of intercellular matrix and decreased depth of blastocyst invasion.…”
Section: Data On the Ivf Results As Affected By Pathologies Of Hemostmentioning
confidence: 99%